RAISING LEVEL OF FLIGHT SAFETY DURING AGRICULTURAL-AIR WORKS - Udartseva, Tatiana (Proceedings of National Aviation University, 2017)
The article presents an analysis of the causes of a serious incident that occurred during the aircraft-chemical works on the An-2 plane. Objective: The aim of this work is to investigate the causes of aircraft collisions with electric power lines during the agricultural-air works and to develop preventive measures. Metods: Using the SHEL model recommended by ICAO, the main and additional causes of the aircraft collision with the electric power line are established. Results: The article contains the results of an analysis of data from investigations of accidents and incidents involving civil aircraft that occurred in Ukraine in 2013 - 2016. During this period, there were five collisions of aircraft with electric power lines, two of them with a fatal outcome. Since such cases are of a non-individual nature, the authors have developed appropriate preventive measures. Discussion: Aviation incident prevention during low-level flights consists of the implementation of the ICAO experience, namely flight crew training programs: cabin crew optimization (CRM) and flight training in conditions close to real (LOFT). The introduction of issues related to real aviation accidents and incidents, as well as the use of air stimulators for training pilots, are proposed in the training programs for small airline pilots. As a precautionary measure, it is proposed to mark the wires of electric power lines with plastic balls according to international practice. It is proposed in the cockpit of the An-2 airplane install the car restorer of the instrument panel to obtain objective information about the flight parameters and simultaneously to write the talks in the cockpit.